Lokakarya Perencanaan Pembelajaran 1 : Program Sekolah Penggerak Angkatan 3 Kota Lhokseumawe - Muhammad Wali; Elfiadi; Burhanuddin; Cut Intan (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
A student-centered approach has become a priority in efforts to improve the quality of education at various levels. Community service activities are carried out with the main purpose of improving the quality of education at Lot 3 of Lhokseumawe City Mobilization School. Through a series of structured steps, the author has identified educational challenges, developed teachers' pedagogical skills, and deepened liberal learning. Study program. Working closely with schools helps design educational programs that are more relevant, enjoyable, and tailored to the needs of students. Close monitoring and evaluation of these programs provides a clear picture of changes taking place and allows for necessary adjustments. As a result, the student-centered approach has succeeded in creating positive changes in the education system of Lhokseumawe City Mobilization School, Lot 3. Teachers and students are well equipped. This success has resulted in a more holistic learning environment, regardless of the level of learning. cultural background or personal circumstances. In addition, this activity contributes to the formation of more capable future leaders in the educational context through the Phase 3 driver's learning program. Overall, this community service has had an impact. has been significantly positive in improving the quality of education in the region and is an inspiration for future efforts to further improve education